Synthesis and antibacterial activity of new hydrazide-hydrazones derived from Benzocaine - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (MARMARA UNIV, FAC PHARMACY, 2017)
A novel series of new eleven benzocaine hydrazide derivatives, N-(4-{[2-(nonsubstituted/ substitutedfuryl/ phenyl/ pyridinyl/ thienyl/ pyrrole) methylidene]hydrazinyl] carbonyl} phenyl) benzamides [3a-k] have been synthesized in this study. The structures of the new compounds were determined by spectral (FT-IR and H-1-NMR) methods and their purity was proven by elemental analysis and thin layer chromatography. These compounds were evaluated for in vitro antibacterial activity by using micro-well dilution method against Escherichia coli ATCC 10536, Escherichia coli ATCC 15442, Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 15442, Acinetobacter baumannii, Klebsiella pneumonia ATCC 13883.
Keywords: Antibacterial activity; Benzocaine; hydrazide-hydrazone; azomethine; BIOLOGICAL-ACTIVITIES; ANTICANCER AGENTS; ANTI-HCV; DERIVATIVES; APOPTOSIS; ETODOLAC